Identifikasi Sektor Ekonomi Strategis Penunjang Pertumbuhan Ekonomi (Pendekatan Analisis Sektor Basis) - Rulan Manduapessy; Fransiska Triyanti Ola (STIE Jambatan Bulan, 2022)
This study aims to determine the strategic economic sectors as a supporter of economic growth in Mimika Regency. To determine the economic growth of Mimika Regency in 2010-2017 and strategic economic sectors to support economic growth in Mimika Regency, the data analysis instruments used in this study were Location Quetient (LQ) analysis, Shift Share analysis and Klassen Typology analysis. During the research year, Mimika Regency's economic growth resulted in a positive change in Shift Share added value of 47,854.64 and had two strategic economic sectors to support Mimika Regency's economic growth. These economic sectors are the agriculture, forestry and fishery sectors, especially in the food crops sub-sector and the marine fisheries sub-sector which dominates the fishery sector; and the economic sector of wholesale and retail trade, repair of cars and motorcycles supported by the issuance of 2,297 trade business licenses and recorded as many as 844 SITU made by the Department of Industry and Trade. The pace of trade activities in Mimika Regency has a good impact on increasing economic growth in Mimika Regency.